Monkeypox: Is the world ready for another pandemic? - Haruna, Usman Abubakar; Musa, Shuaibu Saidu; Manirambona, Emery; Lucero-Prisno, Don Eliseo; Sarría-Santamera, Antonio (Frontiers in Public Health, 2022)
As the world continues to endure the impact of the COVID-19 pandemic, an outbreak of Monkeypox occurs and continues to spread unabatedly. The double-stranded DNA monkeypox virus is a sylvatic zoonosis, which occasionally infects humans and is a member of the genus Orthopoxviruses. Although scientists believed the virus to have low transmissibility, the speed and degree with which it spreads is alarming and could land one in a hospital or even kill one. Additionally, the fact that unusual transmissions are occurring among people without travel history to endemic regions suggests undetected transmissions, raising concerns about our preparedness for another pandemic. Contrary to the COVID-19 pandemic, there is a vaccine that could offer some protection against the monkeypox virus. Therefore, there is a need for coordinated efforts among authorities concerned and community-based organizations to raise awareness of the potential pandemic of monkeypox, activate surveillance systems and laboratory capacity, and heighten contact tracing and vaccination of at-risk individuals to stem the outbreak while there is still the opportunity to prevent it from becoming a pandemic.